IN PURSUE OF A SHORT-TERM EEG NEUROFEEDBACK THEORY: RESEARCH OUTLINE AND FIRST RESEARCH OUTCOMES - Kaplan, Cyril (LIFE: International Journal of Health and Life-Sciences, 2020)
This paper presents an overview of the methodological road map constructed to clarify several reoccurring issues in EEG neurofeedback (NF) research, namely the problems with small samples and with a vast multitude of variables. Data, both qualitative and quantitative, from three studies (n=3, n=7, and n=16) and design of two research steps yet to be completed are presented to illustrate our methodological standing point. Furthermore, we aim to explore the usefulness of conceptualizing neurofeedback experience as a “game” in a research context, in contrast to the prevalent “neurofeedback as treatment” conceptualization. Overview of performed and planned research steps relying on mixed methods work with introspective data and EEG recordings as well as suggestions for direction of future research in the field of EEG neurofeedback are presented together with a brief description of an open-source application for neurofeedback practice and research, an application developed to help to build the short-term EEG neurofeedback theory.